137 Characteristics and outcome of patients with arrhythmias following cardiac transplantation referred for radiofrequency catheter ablation: a two centre experience. (22nd September 2015) - Elsik, M; Teh, A; Parameshwar, Jayan; Virdee, M; Kistler, P; Fynn, S
Abstract : Introduction: Arrhythmias following cardiac transplantation are associated with adverse clinical outcomes. However, the characteristics and outcomes of these patients, and the electrophysiologic mechanisms of these arrhythmias, are poorly defined. Methods: Patients referred for electrophysiological study (EPS) and/or radiofrequency catheter ablation (RFA) between June 2006 and October 2009 (in two major cardiac transplant centres (one in the UK, one in Australia) were identified. Case notes were reviewed retrospectively, and data collected prospectively, to determine demographic characteristics, details of transplantation, arrhythmia diagnosis and treatment, as well as EPS/RFA findings. Data are expressed as mean (SD) or median (IQR). Results: From 2006 onwards, 859 heart transplant patients were under regular cardiac review. A total of 14 patients underwent EPS±RFA. The mean patient age was 52.5 (±13.4) years and 10 were male. Twelve of the 14 had undergone cardiac transplantation (atrial-atrial anastomoses) and two patients had undergone heart/lung transplantation. Primary presenting symptoms were recurrent palpitations±presyncope in 10 patients and tachycardia associated dyspnoea or worsening congestive cardiac failure (CCF) in the remaining four. Arrhythmias were not associated with rejection or coronary artery vasculopathy in 13 of 14 patients, and mild rejection/vasculopathy was noted in 1 of 14. Thirteen of the 14 patients had normal ejection fraction, and one patient presenting with worsening CCF had moderate ventricular dysfunction. DC cardioversion had been performed in 9 of 14 patients, and 13 of 14 had required at least one anti-arrhythmic drug. At EPS, atrial flutter (AFL) was diagnosed and ablated in 5 of 14, atrial tachycardia (AT) from remnant atria/suture line in 4 of 14, AT+AFL in 3 of 14, AVNRT in 1 of 14 and donor heart sinus/crista tachycardia in 1 of 14. Time from transplantation to arrhythmia presentation was 7.8 (±5.3) years, and to EPS a further 1.9 (±1.3) years. 3D mapping was utilised in 6 of 14 patients (one AVNRT, one sinus/crista tachycardia, one AFL and three ATs). At median follow-up of 89 (50–472) days, there were no arrhythmia recurrences and the majority of antiarrhythmic drugs were ceased. One patient died due to progressive CCF. Conclusion: Late presentation of arrhythmias following cardiac transplantation is not associated with rejection. The commonest arrhythmia at EPS is AFL, although a wide spectrum of arrhythmia mechanisms may be encountered. Atrial fibrillation appears to be uncommon. RFA is a highly effective treatment and should be considered early in the management of these patients.